Theory of transformations in steels - Bhadeshia, H. K. D. H., (Harshad Kumar Dharamshi Hansraj), 1953- (Boca Raton : CRC Press, 2021)
"Written by the leading authority in the field, this work is the first to provide readers with a complete discussion of the theory of transformations in steel. It offers comprehensive treatment of solid-state transformations, covering the vast number in steels. It features discussion of physical properties, thermodynamics, diffusion, and kinetics and covers ferrites, martensite, cementite, carbides, nitrides, substitutionally-alloyed precipitates, and pearlite. It also contains a comprehensive list of references as further and recommended reading. With its broad and deep coverage of the subject, this work aims at inspiring research within the field of materials science and metallurgy"--
Includes index.
Keywords: Steel alloys; Physical metallurgy; Phase transformations (Statistical physics)